2007
DOI: 10.1002/jms.1159
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray ionization mass spectrometry monitoring of indigo carmine degradation by advanced oxidative processes

Abstract: The degradation of the dye indigo carmine in aqueous solution induced by two oxidative processes (H(2)O(2)/iodide and O(3)) was investigated. The reactions were monitored by electrospray ionization mass spectrometry in the negative ion mode, ESI(-)-MS, and the intermediates and oxidation products characterized by ESI(-)-MS/MS. Both oxidative systems showed to be highly efficient in removing the color of the dye aqueous solutions. In the ESI(-)-MS of the indigo carmine solution treated with H(2)O(2) and H(2)O(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 36 publications
(29 reference statements)
1
22
0
4
Order By: Relevance
“…The m/z peak at 226 is a characteristic peak of ISA, which can be further converted to the anion of m/z 244 by the addition of H 2 O. Both products of m/z 226 and 244 can be identified during indigo carmine degradation by other methods [32][33][34]. These results are consistent with that of the UV-visible spectra, which revealed the characteristic peak of ISA at 235 nm.…”
Section: Indigo Carmine Decolorizationsupporting
confidence: 80%
“…The m/z peak at 226 is a characteristic peak of ISA, which can be further converted to the anion of m/z 244 by the addition of H 2 O. Both products of m/z 226 and 244 can be identified during indigo carmine degradation by other methods [32][33][34]. These results are consistent with that of the UV-visible spectra, which revealed the characteristic peak of ISA at 235 nm.…”
Section: Indigo Carmine Decolorizationsupporting
confidence: 80%
“…30 Recent examples have shown that ESI-MS, in conjunction with ESI-MS/MS, can be successfully applied to monitor a number of processes, including the environmentally-relevant ones, furnishing novel and significant information about them. [31][32][33][34][35][36][37][38][39][40][41] In this work, ESI(-)-MS (electrospray ionization mass spectrometry in the negative ion mode), in conjunction with ultraviolet-visible spectrophotometry (UV-Vis) and total organic carbon (TOC) techniques, were employed to monitor the reductive degradation of four prototype food dyes: Amaranth (1), Sunset Yellow (2), Red 40 (3) and Brilliant Blue (4) (Figure 1). The reactions were Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Indigo carmine (C18H8N2Na2O8S2) consists of a chromogenic bond of a single C=C double bond substituted by two NH donor groups, with two C=O acceptor groups at the center of the formula [16,24,[33][34][35]. The unsaturated bond is a double bond of carbon in a benzene ring, and the center of the formula of indigo carmine [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the strong chromogenic C=C double bond, which is mainly responsible for the blue color of dye solution, is To confirm the results and clarify the role of voltage amplitude on water surface streamer discharge, we treated an Indigo carmine (IC) organic dye solution as a polluted water sample. Indigo carmine (C 18 H 8 N 2 Na 2 O 8 S 2 ) consists of a chromogenic bond of a single C=C double bond substituted by two NH donor groups, with two C=O acceptor groups at the center of the formula [16,24,[33][34][35]. The unsaturated bond is a double bond of carbon in a benzene ring, and the center of the formula of indigo carmine [23,24].…”
Section: Resultsmentioning
confidence: 99%